2014
DOI: 10.1007/s13571-014-0083-x
|View full text |Cite
|
Sign up to set email alerts
|

On the Estimation of the Distribution Function of a Finite Population Under High Entropy Sampling Designs, with Applications

Abstract: The estimation of the distribution function of a population is an important problem in sampling finite populations. The existing literature focuses on the problem of estimating the population distribution function (p.f.d.) at a single point, or at a finite number of points. In this paper the main interest consists in estimating the whole p.d.f.. In many respects, the starting point is close to classical nonparametric statistics, although the approach to inference is based on sampling design. It is shown here t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 18 publications
(16 reference statements)
0
36
0
Order By: Relevance
“…Let p A ={ p A, i : i =1,…, N } with normalΣi=1NpA,i=nnormalA be the inclusion probabilities for the conditional Poisson sampling design. Given p A , it is possible to find π A ={ π A, i : i =1,…, N } with normalΣi=1NπA,i=nnormalA such that the conditional Poisson sampling design with p A is asymptotically equivalent to the Poisson sampling design with the inclusion probabilities π A (Hájek, 1964; Conti, ). Therefore, for a high entropy design, to apply our theoretical results, we check the conditions for the corresponding inclusion probability π A under Poisson sampling.…”
Section: Asymptotic Results For Variable Selection and Estimationmentioning
confidence: 99%
“…Let p A ={ p A, i : i =1,…, N } with normalΣi=1NpA,i=nnormalA be the inclusion probabilities for the conditional Poisson sampling design. Given p A , it is possible to find π A ={ π A, i : i =1,…, N } with normalΣi=1NπA,i=nnormalA such that the conditional Poisson sampling design with p A is asymptotically equivalent to the Poisson sampling design with the inclusion probabilities π A (Hájek, 1964; Conti, ). Therefore, for a high entropy design, to apply our theoretical results, we check the conditions for the corresponding inclusion probability π A under Poisson sampling.…”
Section: Asymptotic Results For Variable Selection and Estimationmentioning
confidence: 99%
“…Because of its properties, we consider here the classical Hájek estimator of F N : falseF̂H(y)=i=1N1πiDiI(yiy)i=1N1πiDi which is a proper distribution function. Its main asymptotic properties are summarized in proposition , proved in Conti ().…”
Section: Assumptions and Preliminariesmentioning
confidence: 99%
“…Sitter & Wu () showed that the Woodruff intervals perform well even in moderate to extreme tail regions of the distribution function. In fact, as shown in Conti (), the term ( A − 1) p (1 − p ) is essentially the asymptotic variance of the Hájek estimator when y = Q ( p ).…”
Section: Confidence Intervals For Population Quantiles: Asymptotic Apmentioning
confidence: 99%
See 2 more Smart Citations